Finite Element Analysis of Mechanical Clinching Process. (2017) - Jagtap, K.R.; Ghorpade, S.Y.; Chopade, S.E.
Abstract: In this study numerical simulation of the mechanical clinching process is performed by using the FEA software. Clinching is mechanical joining process, performed with simple tools like punch, die and a blank holder. A 2D axisymmetric model is generated for clinching tools and sheets by using LS-DYNA software. The geometry of the clinching tools affects the strength and quality of the final clinch joint. Mechanical clinching is high speed cold forming process, thus, process simulation is difficult task. Load verses displacement graphs are plotted and validation study carried out with experimental results. Parametrical study is performed to acquire best possible results for good mechanical interlock of two aluminium sheets.